Tuberculosis and Cervical Lymphadenopathy: Treatment and Diagnosis - Tanwir, Farzeen; Mazhar, Saima; Bibi , Tauqeer; Baqar , Anum; Khan, Ahmed Bin Khalid; Mahar , Yasmeen; Khalid , Arsalan; Ijaz, Hira; Quereshi, Maryam Faiz; Younus, Areeba; Khan, Mahail; Khattak, Mariya Azam; et al. (Research Highlights in Disease and Health Research Vol. 7, 2023)
This study aims to determine the prevalence of tuberculosis in cases of cervical lymphadenopathy as well as the common presentations and aetiologies of cervical lymphadenopathy. Lymphadenopathy is a common clinical finding in a patient seeking oral health care. It may be in a localized, limited, or generalized form. Malignancies, infections, autoimmune disorders, iatrogenic, and other miscellaneous conditions are considered as the causes for cervical lymphadenopathy. Unexplained cervical lymphadenopathy is a cause of concern for physician and patient because sometimes it could be the manifestation of an underlying malignancy. Tuberculous cervical lymphadenopathy usually presents with multiple lymph node enlargement without constitutional sign. Fine needle aspiration and excisional biopsies are usually done to make a definitive diagnosis. Commonest presentation may be neck swelling (92%), followed by fever, cold abscess, non-healing ulcer, discharging sinus, anorexia and weight loss. The study was conducted from July 2010 to august 2013 at the surgery department of Ziauddin Medical University hospital Karachi, Pakistan. Inclusion criteria included all patients with cervical lymphadenopathy. The data was analyzed by Statistical Package for Social Sciences (SPSS) version 17. In total 220 patients were recruited to participate at the beginning of the study while only 175 patients remained in the study till the investigations were done. Hence study comprised of total 175 participants with response rate of 79.5%. Age range of the participants was 13-69 years that included146 (83.4%) females and 29 (16.6%) males. The maximum patients were in 21-30 years of age group followed by 11-20 years. Cervical lymphadenopathy is prevalent in Pakistan, with most likely diagnosis as Tuberculosis, as seen in majority of the cases. Neck mass, headache and fever are the most frequent presentation of cervical lymphadenopathy. A good follow-up culture is also required to monitor the need for additional diagnostic tests in the setting that a patient fails to respond to appropriate initial therapy.